A prospective, multicenter study of invasive fungal disease caused by molds in children and adults in Chile - Ricardo Rabagliati; Dona Benadof; Luis Thompson; Patricia Garcia; Tamara Gonzalez; Cecilia Vizcaya; Andres Soto; Catalina Gutierrez; Lorena Rodriguez; Yenis Labraña; Cecilia Tapia; Marcela Zubieta; et al. (PLoS ONE, 2025)
Background Invasive mold diseases (IMDs) are a severe complication of immunocompromised subjects and an emerging problem among severely ill, apparently immunocompetent patients. The aim of this study was to describe the epidemiological and clinical features of IMDs in Chile. Methods Prospective study of IMD cases in children and adults from 11 reference hospitals in Chile from May 2019 to May 2021. Results One hundred seventy-six cases were included, 135 in adults and 41 in children, with an overall incidence of 0.4/1,000 admissions. The median age was 10.5 years in children and 56.6 years in adults, with male gender predominance in adults (61.5% versus 41.5%, p = 0.03). Immunosuppression was the most common condition in both children and adults. However, cancer, neutropenia, and hematopoietic cell transplantation were significantly more frequent in the pediatric group. In contrast, diabetes, viral pneumonia, chronic kidney disease, and chronic obstructive pulmonary disease were significantly more frequent among adult patients. Regarding the diagnostic category, 30.1% of cases were proven, 55.7% probable and 14.2% possible. Aspergillosis was the most frequent IMD diagnosed in 75.5% of cases, followed by fusariosis in children and mucormycosis in adults. Viral pneumonia was associated in 40.3% of cases, mainly COVID-19, with aspergillosis in 87.3%. No triazole resistance was observed in Aspergillus spp.. Antifungals were prescribed in 97.2% of the patients: voriconazole 61.4%, liposomal amphotericin 20.5%, combination antifungals 11.1%, and others 6.4%. Overall survival was 68.7%, 61.4%, and 51.7% at 30, 90 and 180 days, respectively. Discussion This is the most extensive study of IMDs in Chile, evidencing an incidence of 0.4 per 1,000 admissions, with aspergillosis being the most frequent infection. Nearly 40% of cases were associated with respiratory viruses, accounting for the impact of COVID-19. Despite almost all patients starting antifungal therapy, the survival rate was poor. It is advisable to start a surveillance program of IMDs in Chile and verify the absence of azole resistance of Aspergillus spp.